2004
DOI: 10.1122/1.1773783
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of short fiber model suspensions

Abstract: International audienceThe rheological behavior of two series of model suspensions containing the same glass fibers in a Newtonian polybutene and in a Boger fluid has also been investigated. The steady-state shear viscosity of both supensions increased with fiber content, but the suspensions in the Boger fluid became shear thinning. Both types of suspension exhibited non-negligible normal stresses. The steady-state viscosity and normal stress difference of the supensions in the polybutene are well predicted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
88
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 35 publications
26
88
0
2
Order By: Relevance
“…Different explanations have been proposed to explain the departure from a Newtonian response. These include arguments that the fibres were not rigid under the imposed conditions (Powell 1991;Sepehr et al 2004) or that the fibres are not force-free. An example of the latter is the assertion that adhesive forces (Mongruel & Cloitre 1999;Chaouche & Koch 2001;Bounoua et al 2016b) can exist between the fibres, even though their size is large compared to typical colloidal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Different explanations have been proposed to explain the departure from a Newtonian response. These include arguments that the fibres were not rigid under the imposed conditions (Powell 1991;Sepehr et al 2004) or that the fibres are not force-free. An example of the latter is the assertion that adhesive forces (Mongruel & Cloitre 1999;Chaouche & Koch 2001;Bounoua et al 2016b) can exist between the fibres, even though their size is large compared to typical colloidal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Wie in [9,12] [20,21]. Daher wurde eine Modellerweiterung vorgeschlagen, wobei der Geschwindigkeitsgradient mit einem konstanten Faktor skaliert wird [20,21].…”
Section: Unterteilung Von Suspensionenunclassified
“…Daher wurde eine Modellerweiterung vorgeschlagen, wobei der Geschwindigkeitsgradient mit einem konstanten Faktor skaliert wird [20,21]. Dieser Ansatz wird auch als "reduced strain closure" (RSC) bezeichnet.…”
Section: Unterteilung Von Suspensionenunclassified
“…The results clearly showed that at low shear rates, increasing volume fractions and/or fibre aspect ratios leads to increase the viscosity, whereas at high shear rate the suspension viscosity approach to that of suspending viscoelastic fluids and almost independence of fibre characteristics. More recently, Sepehr et al [16] have done some experiments of fibre suspended into both Newtonian and Boger fluids. The results show that shear-thinning behaviour occurs strongly in Boger solvent but is only lightly observable in Newtonian solvent and the suspension viscosity seems to approach that of the suspending viscoelastic fluid at very high shear rates.…”
Section: Introductionmentioning
confidence: 98%
“…0045 The fibre-suspended fluids in question are shear thinning, so that the shear viscosity decreases with increasing shear rates. Some modelling effort has been directed to this problem [11][12][13][14][15][16]. Azaier [13] successfully simulated fibre suspensions in polymeric liquids modelled by different models (FENE-P, FENE-GR and Giesekus models), their numerical results showed that the ratio of the suspension viscosity and the solvent viscosity is almost constant over whole range of shear rates even at high shear rates that is not observed in several other experiments done by Chan et al [11], Ganani and Powell [12] and Ramazani et al [15].…”
Section: Introductionmentioning
confidence: 99%